Didactic Phenomenon-based Learning through Scientific Approach to Improve Students' Communication Skills - Lukman Nulhakim; Nurul Anriani; Sholeh Hidayat (Gagasan Pendidikan Indonesia, 2022)
One of the abilities to think mathematically is the ability to communicate. This ability is an important part of education. This research started with the mathematics teaching materials used that did not facilitate students to have the opportunity to explore, make conjectures and test these conjectures. Learning mathematics based on didactic phenomena through a scientific approach based on students' initial mathematical communication skills (MCS) will greatly determine the achievement of learning objectives. This study aimed to determine differences in the achievement of mathematical communication skills between students who receive didactic-based mathematics learning through a scientific approach and students who receive conventional mathematics learning. Also, to find out that there are differences in self-confidence between students who receive didactic-based mathematics learning through a scientific approach and students who obtain mathematics learning with a conventional approach. This study used a quantitative research method with a quasi-experimental research design with the type of Pretest – Posttest Control Group Design. The results of this study are the analysis of the mathematical communication abilities of students who receive didactic-based mathematics learning with conventional learning.